COVID‐19 disease trajectories among nursing home residents. Issue 9 (7th June 2021) - Carnahan, Jennifer L.; Lieb, Kristi M.; Albert, Lauren; Wagle, Kamal; Kaehr, Ellen; Unroe, Kathleen T.
Abstract: Introduction: Older adults are at greater risk of both infection with and mortality from COVID‐19. Many U.S. nursing homes have been devastated by the COVID‐19 pandemic, yet little has been described regarding the typical disease course in this population. The objective of this study is to describe and identify patterns in the disease course of nursing home residents infected with COVID‐19. Setting and Methods: This is a case series of 74 residents with COVID‐19 infection in a nursing home in central Indiana between March 28 and June 17, 2020. Data were extracted from the electronic medical record and from nursing home medical director tracking notes from the time of the index infection through August 31, 2020. The clinical authorship team reviewed the data to identify patterns in the disease course of the residents. Results: The most common symptoms were fever, hypoxia, anorexia, and fatigue/malaise. The duration of symptoms was extended, with an average of over 3 weeks. Of those infected 25 died; 23 of the deaths were considered related to COVID‐19 infection. A subset of residents with COVID‐19 infection experienced a rapidly progressive, fatal course. Discussion/Conclusions: Nursing home residents infected with COVID‐19 from the facility we studied experienced a prolonged disease course regardless of the severity of their symptoms, with implications for the resources needed to care for and support of these residents during active infection and post‐disease. Future studies should combine data from nursing home residents across the country to identify the risk factors for disease trajectories identified in this case series.